Well-posedness and stability of solutions for set optimization problems. (2nd January 2017) - Han, Yu; Huang, Nan-jing
Abstract: In this paper, some characterizations for the generalized l - B -well-posedness and the generalized u - B -well-posedness of set optimization problems are given. Moreover, the Hausdorff upper semi-continuity of l -minimal solution mapping and u -minimal solution mapping are established by assuming that the set optimization problem is l - H -well-posed and u - H -well-posed, respectively. Finally, the upper semi-continuity and the lower semi-continuity of solution mappings to parametric set optimization problems are investigated under some suitable conditions.